The Principal Strategy in Improving Teacher Personality Competence: Strategi Kepala Sekolah dalam Meningkatkan Kompetensi Kepribadian Guru - Fahrur Rozi; Akhtim Wahyuni; Eni Fariyatul Fahyuni (Universitas Muhammadiyah Sidoarjo, 2021)
Teachers have a very important role in improving the quality of education in schools. Therefore, strategies appropriate principals are highly demanded to improve teacher competence. The purpose of this research to describe the principal’s strategy in improving the personality competence of teachers at Multilingual Anak Saleh Sedati elementary schools. The research method was qualitative. The result showed that principal made a teacher personality up grading program. The program consists of: coaching, training, assignments and supervision. The up grading program increases the personality competence of teachers who are steady and stable, mature, wise, dignified and have a noble character. This research is expected to add insight and knowledge about the principal’s strategy in improving teacher personality competence.